A representação de jovens estudantes no Conselho Estadual de Educação de Mato Grosso : impasses e perspectivas político-pedagógicas - Costa, Rosa Maria Corrêa da (2004)
This research intends to acknowledge how young student representants from high school and university build-up and understand their participation in the first management where a space was opened for them in the Mato Grosso State Education State Council. The chronological cut which goes from 1999 to 2002 has the objective of showing alterations ocurred in the structure of the Council in this period and the alterations in its law and functioning dinamics which allowed, for the first time in 1998, the representation of students in the Civilian Society segment. One of the great achievements of the 1988 Federal Constitution was the criation of Institutionalized Councils. Being political participation instruments, control and supervision in the appliance of public resources, they must work as a space for negociation of public policies. The councils may be constituted in enriching instances in the building-up of knowledge and the encouragement of citizens in participating and making decisions with collective concern. The young students, in formation in the process of knowledge acquiring, may also have in these places, a space for the development of a political conscience. The information about this theme, after 1995, period of creation of most institutionalized collegiums and the restructuring of the prior existing ones, such as the educational collegiums, are still very defective and focused. There is no argument about this theme in the Mato Grosso State. The questioning which set the research going was knowing if, in this first management, the student representants articulated themselves with the mobilizations of the young students organized in the state. The assumption is that the counselors, when making decision in plenary, do not do it in an articulated way with their basis and in agreement with the public policies definitions for education. To reach the objective of the research, which is situated in a qualitative perspective; a bibliographic, documental and empiric raising was made about the themes related to the implementation and structuring of the Deliberative Councils in Brazil and in Mato Grosso. From the problem initially described and the hipothesis raised, I conclude that the student counselors, do not act in an articulated way with the basis of the student movement in the state and even less in relation to the country. Their actions and decisions are individualized. They act in a way of endorsing paternalist attitudes from teachers. They participate timidly in discussions about the elaboration of sectorial policies. They participate but do not represent their segment.